Immunomodulator Effect of Cnidoscolus aconitifolius Leaves Extract on CD4+ and CD8+ Expression in Salmonella typhimurium infected mice - Hidayati, Sholihatil; Susanti, Dhina Ayu; Destiawan, Rian Anggia; Muflihah, Ahdiah Imroatul; Handayani, Rizka; Anggitasari, Wima (Universitas Ahmad Dahlan, 2024)
Typhoid fever is a common health problem in the community caused by Salmonella bacteria. The incidence rate of this infection will increase if a person's immune system is weakened. Plant extracts are generally considered to be potential immunomodulatory agents developed, which have smaller side effects. Research shows that Cnidoscolus aconitifolius leaves have medicinal properties including as hepatoprotective, antidiabetic, and anticardiovascular. The results of the antioxidant activity test show the results that Cnidoscolus aconitifolius leaves extract (CAE) has potential as an antioxidant with a very strong category. This study was conducted to determine the effect of giving Japanese papaya leaf extract on CD4+ and CD8+ expression in Babl/c mice induced by Salmonella typhimurium bacteria. The study was started by preparing 70% ethanol extract from Cnidoscolus aconitifolius leaves and preparing 30 Babl/C mice as experimental animals which were divided into 6 groups (healthy control, negative control, positive control and treatment group by giving CAE dose of 100 mg/kgbw, 200 mg/kgbw and 400 mg/kgbw). Induction was carried out by oral infection with Salmonella thypimurium bacteria. After 3 days the infected mice were treated orally once a day for 7 days. Evaluation of CD4+ and CD8+ expression was carried out using the flowcytometer method of the lymph organs. Data analysis was carried out by the Anova test followed by the post hoc test (Tukey) using the SPSS for Windows application. The results showed that giving CAE at doses of 100 mg/kgbw, 200 mg/kgbw and 400 mg/kgbw could increase the expression ratio of CD4+ and CD8+, whereas giving CAE at a dose of 400 mg/kgbw showed significantly different results (p<0.05) to the negative control. This shows that the CAE has potential as an immunomodulatory agent that can improve immune function.